Development of Android-Based Sikair Interactive Learning Media to Improve Students' Learning Outcomes in The Water Cycle - Widya Septiani; Budi Hendrawan; Rahmat Permana (Journal of Future Education, 2023)
This study aims to develop a product in the form of interactive learning media based on Android to improve student learning outcomes in elementary schools. This study uses the Research and Development method. This research was conducted at SDN 2 Courts. The results of the validation of the Android-based interactive interactive media were carried out by experts such as material experts, media experts and linguists. Each expert is as follows: the material expert gives a final score of 1 with the eligibility criterion of 100% or can be said to be "Very Eligible", the media expert gives a score of 0.9 with the eligibility criterion of 90% or can be said to be "Very Eligible", and the linguist gives a score of 1 with the eligibility criteria of 100% or you could say "Very Eligible". The results of the small group trials obtained an average score of 88.5% with the eligibility criteria "Very Eligible", and the results of the large group trials obtained an average score of 90.5% with the eligibility criteria "Very Eligible". This shows that the Android-based interactive sikair learning media is very suitable to be used as a natural science learning media, especially in water cycle material, the field research stage of the Android-based interactive sikair media obtained an average N-gain score of 0.8 in the "High" category and "Effective interpretation category". Based on the results obtained, the Android-based interactive interactive media was declared feasible and effective for use in elementary schools.